2012
DOI: 10.5014/ajot.2012.004291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Life Review Writing on Depressive Symptoms in Older Adults: A Randomized Controlled Trial

Abstract: OBJECTIVE. We examined the effects of engaging in the occupation-based intervention of life review through writing on expressed depressive symptoms as measured with the Geriatric Depression Scale in older adults residing in senior residences. METHOD. The study design was a randomized controlled trial that took place in four senior residences in New York City. Forty-five participants (23 treatment, 22 wait-list control) ≥65 yr old participated in the 8-wk, once-weekly autobiographical writing wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 38 publications
0
39
0
1
Order By: Relevance
“…Even without a clinical diagnosis of major depression, individuals who have depressive symptoms often experience a significant decline in independence, functional performance of activities of daily living, and overall health (Chippendale & Bear-Lehman, 2012). Research has shown that as many as 27% of older adults who live in a senior residence exhibit symptoms of depression (Chippendale & Bear-Lehman, 2012). Due to this prevalence and the devastating and expansive effects of depressive symptoms, early intervention and treatment is crucial.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Even without a clinical diagnosis of major depression, individuals who have depressive symptoms often experience a significant decline in independence, functional performance of activities of daily living, and overall health (Chippendale & Bear-Lehman, 2012). Research has shown that as many as 27% of older adults who live in a senior residence exhibit symptoms of depression (Chippendale & Bear-Lehman, 2012). Due to this prevalence and the devastating and expansive effects of depressive symptoms, early intervention and treatment is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to identify health care professionals and interventions that can address depressive symptoms and their impact on occupational engagement and function. The current literature recognizes occupational therapy as an appropriate profession for addressing the psychosocial and occupational needs of individuals (Chippendale & Bear-Lehman, 2012;AOTA, 2014). Two interventions within the scope of occupational therapy practice that have been utilized to address the occupational deficits caused by depressive symptoms include life review and reminiscence therapy (Harwood, 1989;StevensRatchford, 1992;Chin, 2007).…”
Section: Occupational Therapy Interventions: Life Review and Reminiscmentioning
confidence: 99%
See 3 more Smart Citations